Perbaikan Proses Bisnis Pasang Baru Telepon Kabel di Wilayah Pemasangan Baru Surakarta dengan Metode Fault Tree Analysis - Wahyudi Sutopo; Retno Wulan Damayanti (Performa: Media Ilmiah Teknik Industri, 2007)
TELKOM always make an effort to fulfill the society need upon products and services of fixed phon. The effort of TELKOM such as repair the old network (existing) and add the new network in certain area that have high potency of demand, such as in Gentan, Purbayan, Colomadu, Jaten and Kaliyoso. Those reparation and increament of the network give chances to customer of TELKOM who want to have a new installation of fixed phone (PSB). Process of PSB fixed phone in existing area is different with new network area. In new network area, TELKOM not yet had standard business process, and this is stimulate some problems, such as delayed activation, untidy network, lack of access of network and escalation (fatal cancel).Evaluation and improvement of business process are required in order to prevent and to reduce some problems. Evaluation and improvement of business process are conducted using the method of Fault Tree Analysis (FTA) and Malcolm Baldrige National Quality Award (MBNQA). Based on the result of FTA and MBNQA, there is improvement on business process new installation (PSB) of fixed phone in new network area by adding Drop Wire withdrawl in early stage.